Modal Sosial untuk Keberhasilan Madrasah Diniyah dalam Penyemaian Ideologi ke-Islaman dan Jawa - Subhin, M. Abdillah; Ikhwan, Afiful; Anwar, Saiful (Jurnal Pendidikan Nusantara, 2022)
Madrasah Diniyah Zumrotus Salamah since this educational institution emerged in the classical period, and its development is grappling with modernity while maintaining its identity as an Islamic educational institution which is a place for seeding Islamic and Javanese ideologies. This research focuses on social capital practised in Madrasah Diniyah Zumrotus Salamah as an institutional effort to instil Islamic and Javanese ideology. Using a qualitative and phenomenological approach, data were collected through in-depth interviews, observation and documentation. Data were analyzed by content analysis using an inductive approach and validity checking by data triangulation. The results of this study indicate that amid today's modernization, many individuals are far from morality. Through education at the Zumrotus Salamah Madrasah with the hybridization of the teachings of Religion and Javanese Custom, it is hoped that it can become a vessel for increasing self-religious piety. Islamic Dates and Dates of Perdikan Tawangsari Village, Adornment of body and clothing and Self-awareness of ana ing lathi, Study of Jawi culture is a social capital provided by Madrasah Diniyah Zumrotus Salamah to the students.